Algoritma Welch-Powell Untuk Pewarnaan Graf pada Penjadwalan Perkuliahan - Yulianti Rusdiana; Alfi Maulani (SPEJ (Science and Physic Education Journal), 2019)
Scheduling is a principal administrative activity in most universities. The problem that often faced is the lecture timetable and course distribution are still manually and have not fully paid attention to the field of science that matches the interests of the lecturer. To overcome these problems, the authors use Welch-Powell's algorithm to arrange lecture arrangement schedules with expectations that the scheduling will be faster and optimal and more satisfying to various parties. The results of applying Welch-Powell's Algorithm to the willingness of lecturers to teach available courses provide four colors. The results are used to map lecturers and subjects that are supported by class availability to ensure that lecturers with the same course choices must be placed in different classes. In meeting class needs, one lecturer can handle several subjects, and several lecturers can teach one subject. The results of applying the Welch-Powell Algorithm to the suitability of teaching time give 29 colours. These results are used to map lecture time to ensure that lecturers with the same choice of time should be provided in different classes. Keywords: Vertex, Colouring, Welch-Powell's algorithm